The Role of Lymph-vascular Space Invasion towards Disease of Free Survival and Overall Survival Cancer in High-Risk Endometrial Cancer Endometrioid Type Patients - Brahmana Askandar, - (Wolters Kluwer Medknow Publications, 2020)
Major prognostic factors of endometrial cancer include stage, age, histopathological type, grading, depth of invasion of myometrium, and presence of Lymph-vascular Space Invasion (LVSI). This study evaluated the LVSI in disease free survival (DFS) and overall survival (OS) in high-risk endometrial cancer endometrioid type. This was a retrospective study. Survival analysis using Kaplan-Maier curve, log rank test, cox-regression and logistic regression were used to determine effects among variables. Among fifty-six patients, 43% of patients were <60 years, 73% with BMI <30, 17% were multiparous, and 79% were menopausal patients. There were 32% of patients with positive LVSI. Most clinical stages were found in stage III with 31 cases (55%). Patients with positive LVSI had OS lower than patients with negative LVSI (50% vs 55.3%). There were no significant results of LVSI as prognostic factor for OS. Patients with LVSI positive had survival time of 26.5 months (20.5 – 32.5). There were no significant results of LVSI as prognostic factor for DFS. Patients with positive LVSI had lower DFS than patients with negative LVSI (81.8% vs 85.7%). There were significant results of LVSI as prognostic factor for high-risk endometrioid type endometrial cancer with stage endometrial cancer with p = 0.01. LVSI acts as prognostic factor for high-risk endometrioid type endometrial cancer associated with stage endometrial cancer. However, there was no effect in DFS and OS.